1972
DOI: 10.1542/peds.50.1.50
|View full text |Cite
|
Sign up to set email alerts
|

The Small-for-Date Infant. Ii. Neurological and Intellectual Sequelae

Abstract: A prospective study has been done on 96 full term small-for-date infants to determine the incidence and type of neurological and intellectual sequelae. Major neurological defects were uncommon with an incidence of 1% for cerebral palsy and 6% for convulsions. Minimal cerebral dysfunction characterized by hyperactivity, a short attention span, learning difficulties, poor fine coordination and hyper-reflexia was diagnosed in 25%. EEG abnormalities predominantly of a diffuse mild nature were seen in 59% of the bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1978
1978
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 351 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The particular neonatal factors shown in Table 2 were singled out for examination because of their long history as indicators of risk. Birthweight and gestational age are indices of the severity of prematurity, head circumference of brain growth (Hack & Breslau, 1986), small size for gestational age (SGA) of fetal growth retardation (Fitzhardinge & Steven, 1972), Apgar scores of asphyxia, and length of hospitalization of overall severity of early illness (Sell, Gaines, Glucksman & Williams, 1985). RDS, which has a high incidence in our sample, is widely considered one of the major neonatal problems of very low birthweight infants (Hunt, Tooley, & Harvin, 1982); its severity is indicated by time on a respirator, continuous positive airway pressure (CPAP), and oxygen.…”
Section: Methodsmentioning
confidence: 99%
“…The particular neonatal factors shown in Table 2 were singled out for examination because of their long history as indicators of risk. Birthweight and gestational age are indices of the severity of prematurity, head circumference of brain growth (Hack & Breslau, 1986), small size for gestational age (SGA) of fetal growth retardation (Fitzhardinge & Steven, 1972), Apgar scores of asphyxia, and length of hospitalization of overall severity of early illness (Sell, Gaines, Glucksman & Williams, 1985). RDS, which has a high incidence in our sample, is widely considered one of the major neonatal problems of very low birthweight infants (Hunt, Tooley, & Harvin, 1982); its severity is indicated by time on a respirator, continuous positive airway pressure (CPAP), and oxygen.…”
Section: Methodsmentioning
confidence: 99%
“…Dysmature term infants who survive are commonly mentally retarded and often develop patterns of minimal brain dysfunctions (Drillien, 1961(Drillien, , 1972Harper & Wiener, 1965). Fitzhardinge and Steven (1972), in a prospective study of 96 full-term low-birthweight infants, reported that 25 percent developed minimal brain dysfunctions, with hyperactivity, short attention span, and learning difficulties. The EEC was abnormal in 66 percent of the children tested.…”
Section: Sequels Of Perinatal Nervous System Injury: Clinical-patholo...mentioning
confidence: 99%
“…Cerebral palsy is marked by the gyrating motor distortions of athetosis as well as by spastic motor paralysis. Likewise, with regard to mental function, it is increasingly evident that complications in the perinatal period that affect the cerebrum may not only result in abridgement of function, but may also lead to derangement of function, to the development of behavioral disorders (Bender & Faretra, 1961;Dalen, 1965;Drillien, 1961;Fitzhardinge & Steven, 1972;Garmezy & Streitman, 1974;Mednick, 1970;Pasamanick, Rogers, & Lilienfeld, 1956;Rosen, 1969;Taft & Goldfarb, 1964;Torrey, Hersh, & McCabe, 1975. ) Experimentally, in animals surviving after perinatal hypoxic cerebral damage, in addition to sensory, motor, and cognitive defects and the occurrence of seizures, there may develop hyperactivity and other changes in emotional behavior (Kling, 1970;Windle, 1957Windle, , 1966.…”
mentioning
confidence: 99%
“…Not surprisingly, these deficits in cognitive functioning have also been associated with poor school performance (e.g., Cohen, 1986; Corrigan, Berger, Dienstbier, & Strok, 1967; DeHirsch et al, 1966; Fitzhardinge & Steven, 1972; Frances-Williams & Davies, 1974). Moreover, difficulties in school performance have been found to be more common in high-medical-risk children who do not show deficits in intelligence (Fitzhardinge & Steven, 1972; Rubin, Rosenblatt, & Balow, 1973). It appears, then, that high-medical-risk children can be expected to perform relatively more poorly in school than low-risk children, and that these school problems will be observed whether or not the children also demonstrate concomitant reductions in general intelligence.…”
mentioning
confidence: 99%
“…Although deficient performance for high-medical-risk children has been observed in all skill areas, the most consistent deficits have been obtained in tasks that assess visual-motor skills, such as the performance section of the WISC-R or the Bender-Gestalt test (e.g., Bjerre & Hansen, 1976; Caputo, Goldstein, & Taub, 1979; Cohen, 1986; DeHirsch, Jansky, & Langford, 1966; Hunt, Tooley & Harvin, 1982; Klein, Hack, Gallagher, & Fanaroff, 1985; Lis, 1969; Siegel, 1983a; Taub, Goldstein, & Caputo, 1977; Wiener, Rider, Oppel, Fischer, & Harper, 1965; Wiener, Rider, Oppel, & Harper, 1968). Not surprisingly, these deficits in cognitive functioning have also been associated with poor school performance (e.g., Cohen, 1986; Corrigan, Berger, Dienstbier, & Strok, 1967; DeHirsch et al, 1966; Fitzhardinge & Steven, 1972; Frances-Williams & Davies, 1974). Moreover, difficulties in school performance have been found to be more common in high-medical-risk children who do not show deficits in intelligence (Fitzhardinge & Steven, 1972; Rubin, Rosenblatt, & Balow, 1973).…”
mentioning
confidence: 99%